2022
DOI: 10.3390/app12167957
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Optimization of Inulin and Polyphenol Extraction from Artichoke (Cynara scolymus (L.)) Solid Wastes

Abstract: Artichoke wastes after processing represent 60–70% of the raw material and are a potential source of inulin and polyphenols, bioactive compounds that can be valorized as food ingredients or nutraceutical products. The aim of this work was to assess and optimize the extraction of these compounds from artichoke wastes using water or water–ethanol mixtures as extracting agents. For simultaneous inulin and polyphenol extraction and to achieve high antioxidant activity in extracts, the best process conditions using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Jiménez-Moreno and co-workers recovered around 2500 ppm of phenolic components from the waste material of artichoke bracts, outer leaves, and stems [ 25 ]. By setting a water-based extraction protocol, Garcia-Castello et al [ 26 ] revealed that it was possible to recover 60% of the polyphenolic quantity and 56% of antioxidant activity from the solid waste of artichoke by-products. Using ultrasound-assisted procedures, Turker et al [ 27 ] extracted a remarkable quantity of polyphenols from artichoke waste in a shorter time than traditional extraction methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiménez-Moreno and co-workers recovered around 2500 ppm of phenolic components from the waste material of artichoke bracts, outer leaves, and stems [ 25 ]. By setting a water-based extraction protocol, Garcia-Castello et al [ 26 ] revealed that it was possible to recover 60% of the polyphenolic quantity and 56% of antioxidant activity from the solid waste of artichoke by-products. Using ultrasound-assisted procedures, Turker et al [ 27 ] extracted a remarkable quantity of polyphenols from artichoke waste in a shorter time than traditional extraction methods.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the rate of artichoke-derived waste (i.e., roots, stems, bracts, and external leaves) generated during industrial processes is around 70–85% of the plant weight [ 24 ]. Because artichoke by-products are still enriched in beneficial phenols with recognized antioxidant, antiradical, anticarcinogenic, and antiapoptotic properties, the recent literature supports the application of various methodologies involving phenolic molecule recovery [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximate Percentage of Waste from Raw Material (w/w) References Banana peel 30 [5] Apple (pomace, skin, seeds, stem) 25-30 [6,7] Citrus (orange, lemon, grapefruit-pomace, peel, seeds) 50 [8,9] Exotic fruits (pineapple, mango, mangosteen-skin, core, peel, stone) 35-60 [10][11][12] Artichoke (bracts, stem, leaves) 60 [13,14] Asparagus spear 40-50 [15] Potato peel 15-40 [5] Corn cob 20-30 [16] Nevertheless, considering the market value of these components, fertilisers and animal feeds are not necessarily making the most of these resources. Realising the values of the compounds that can be derived from horticultural by-products, shifting in residue handling, has arisen during the last few decades [17].…”
Section: Sources Of Solid Wastesmentioning
confidence: 99%
“…Another study (ultrasonic-assisted extraction at 70 • C, 37 Hz for 30 min) reported the bracts gave 7.5 g inulin/100 g waste whereas the stem gave insignificant amounts and demonstrated that the yield was affected by seasonality [64]. Garcia-Castello et al [13] compared the effectiveness of water and ethanol-water extraction in recovering inulin from artichoke waste. These authors demonstrated that, at optimal conditions, higher inulin yield (approximate 40%) was obtained from water extraction (89 • C, 139 min) than from ethanol-water extraction (22.4% ethanol, 80 • C, 217 min) [13].…”
Section: Inulin and Fructooligosaccharidesmentioning
confidence: 99%
“…However, these by-products are high in many phytochemicals similar to those of its edible flower heads including phenolic compounds, [ 14 , 15 , 16 ], inulin [ 17 ], and dietary fibre [ 18 ]. Based on interest in renewable resources of pharmaceutically active biomolecules, many investigations have been conducted on recycling and the optimisation of the downstream processes for maximal exploitation of artichoke biowastes [ 10 , 19 , 20 , 21 , 22 , 23 ]. However, most of these studies have focused their attention mainly on the bracts, giving little importance to the leaves which, although to a lesser extent, represent a huge waste.…”
Section: Introductionmentioning
confidence: 99%